Evaluación de la aplicabilidad de especies forestales de la serranía peruana en fitorremediación de relaves mineros - Paredes Mur, Javier (2018)
Phytoremediation is a low cost remediation technology used to decontaminate soils from heavy metals. In this study, the use of forest species from the Peruvian Andes (Acacia visco, Buddleja coriacea, Eucalyptus globulus, Myoporum laetum, Polylepis racemosa and Schinus molle) for the treatment of mine tailings, was evaluated. The development of the species in the mining waste was evaluated for 27 weeks, and the pH and concentration of chemical elements were analyzed. The employed species demonstrated a great grow tolerance in contaminated soils, and was removed chemical elements, such as antimony (Sb), arsenic (As), cadmium (Cd), copper (Cu), silver (Ag) and lead (Pb).